Between Profit and Value: Can Capital Structure Carry the Weight? - Nianty, Dara Ayu; DM., Rustan; Sylvia, Sylvia (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
The Jakarta Islamic Index (JII) showcases firms with strong competitive advantage and investment appeal grounded in transparency and Sharia compliance. This study deepens understanding of capital structure dynamics by analyzing how profitability and growth opportunities shape firm value, both directly and through financial leverage. Drawing from a sample of 60 observations across 30 listed JII firms, the study employs panel data path analysis to test hypothesized relationships. Findings reveal that both profitability and growth opportunity significantly influence capital structure and firm value. Moreover, capital structure independently affects firm value, though it does not mediate the impact of the two antecedents. These insights refine capital structure theory in an Islamic equity context and illuminate the nuanced role of financial strategy in value creation. Practically, the results guide investors in screening high-potential Sharia-compliant firms and support managers in crafting funding strategies aligned with both financial performance and Islamic principles.